Concept of counseling for indigenous Bugis culture from Kajaolaliddong thought - Aswar, Aswar; Amirullah, M.; Wijaya Nur, Edil (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2023)
Cultural bias often occurs in implementing counseling in schools, so providing services to counselees is less than optimal.; this occurs due to the counselor’s need for knowledge and understanding of clients from specific cultural backgrounds, including clients from Bugis cultural backgrounds. This research aims to identify the Bugis cultural conception of counseling from Kajaolaliddong’s thoughts in his dialogue with Arumpone (king of Bone). The research method used is a qualitative approach with the Gadamerian hermeneutic research method type, which refers to part and whole analysis in understanding and interpreting texts. The research found the concept of human nature, the ideal and problematic personality, and the criteria for Bugis counselors from Kajaolaliddong’s thoughts. Human nature is found in the concepts of Ade’, Speech, Rapang, and Wari; The concept of the ideal person is found in the concepts of Lempu’ na Sabbi Obbie, Acca’ na Sabbi Gauq’, dan De na Pojiwi Sisala-salae; The concept of a problematic personality is found in the concepts of Dena Talinge, Teani Ripakainge, Madongo, Masekkang, Makkelo Elo, Tenna Maseiwi Tau-e, Matanre Cinna, dan Napojiwi Sisala-Salae. The Bugis counselor criteria are found in the concepts of Ininnawa Deceng, Macca Mpinru, Macca Duppai Ada, dan Poada Ada Tongeng. The implications of this research can be used as material for developing Bugis culture-based counseling in schools to provide guidance and counseling services to counselees with a Bugis cultural background.